2014
DOI: 10.1016/j.bbamem.2013.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular location of the coupling protein TrwB and the role of its transmembrane domain

Abstract: Conjugation is the most important mechanism for horizontal gene transfer and it is the main responsible for the successful adaptation of bacteria to the environment. Conjugative plasmids are the DNA molecules transferred and a multiprotein system encoded by the conjugative plasmid itself is necessary. The high number of proteins involved in the process suggests that they should have a defined location in the cell and therefore, they should be recruited to that specific point. One of these proteins is the coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 55 publications
0
17
1
Order By: Relevance
“…The biological relevance of these findings remains to be evaluated, but it should be noted that several studies have identified functions of the various T4CP domains that could contribute-directly or indirectly-to substrate binding. The NTDs, for example, are unlikely to directly bind substrates, but studies have identified several NTD functions, including binding interactions with other channel subunits, stimulatory effects on T4CP oligomerization and catalytic activity, and contributions to T4CP spatial positioning in the cell (17,(64)(65)(66)(67), that could indirectly affect substrate docking. By virtue of their possible accessibility to secretion substrates in the cytoplasm, the NBDs and CTDs might coordinate with the AAD to recruit substrates through direct substrate engagement.…”
Section: Discussionmentioning
confidence: 99%
“…The biological relevance of these findings remains to be evaluated, but it should be noted that several studies have identified functions of the various T4CP domains that could contribute-directly or indirectly-to substrate binding. The NTDs, for example, are unlikely to directly bind substrates, but studies have identified several NTD functions, including binding interactions with other channel subunits, stimulatory effects on T4CP oligomerization and catalytic activity, and contributions to T4CP spatial positioning in the cell (17,(64)(65)(66)(67), that could indirectly affect substrate docking. By virtue of their possible accessibility to secretion substrates in the cytoplasm, the NBDs and CTDs might coordinate with the AAD to recruit substrates through direct substrate engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MobB CloDF13 was also expressed in the presence of plasmid pSU1456 and to mimic the in vivo transfer of CloDF13, its location was additionally studied in the presence of plasmids pSU1456 (R388 plasmid that lacks TrwB R388 protein) and pSU4833 (CloDF13 plasmid that contains its mobilization region except for MobB CloDF13 protein). Sample handling was performed as described by Segura et al (2014). The images were acquired in a Leica TCS SP5 confocal fluorescence microscope, with a 60× oil immersion objective.…”
Section: Subcellular Location Of T4cpsmentioning
confidence: 99%
“…Studies about subcellular location of different T4CPs reported up to now have rendered ambiguous results (Kumar and Das, 2002;Gunton et al, 2005;Segura et al, 2014). To gain a deeper knowledge of this matter, specifically regarding the role of the TMD, we have studied the subcellular location of TMD TraJ CD TrwB , MobB CloDF13 , and MobB TMD under different experimental conditions.…”
Section: Subcellular Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…Each monomer is composed of two main structural domains: the nucleotide-binding domain showing a RecA-like fold, and a small membrane-distal all-alpha domain. The TMD of TrwB plays an important role in TrwB structural integrity and oligomerization (Hormaeche et al 2002;Hormaeche et al 2004;de Paz et al 2010;Vecino et al 2011), subcellular localization 5 (Segura et al 2014), and regulation of ATPase activity (Hormaeche et al 2006;Vecino et al 93 2010). 94 A coupling role for T4CPs is supported by early genetic data (Cabezón et al 1997) and evidence of protein-protein interactions with both the substrate and the T4SS.…”
mentioning
confidence: 99%